2018
DOI: 10.1002/chem.201705984
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted, Asymmetric Synthesis of 3‐Amino‐2,3‐Dihydrobenzofuran Flavonoid Derivatives from Chalcones

Abstract: A route to access 3-amino-2,3-dihydrobenzofurans that utilizes microwave-assisted organic synthesis to rapidly generate analogues has been developed. The route begins with an acid-catalyzed, microwave-assisted aldol condensation to generate chalcone intermediates, followed by a Corey-Bakshi-Shibata reduction and subsequent Sharpless asymmetric epoxidation to access stereoisomeric epoxyalcohols. The final step is a one-pot, microwave-assisted, regioselective, acid-catalyzed epoxide opening with various amines f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…In the synthesis of the benzofuran derivatives, a one-pot, two-step reaction was implemented. [40] Eu(OTf) 3 catalyzed the epoxide opening with various amines followed by nucleophilic aromatic substitution using Cs 2 CO 3 to generate the benzofurans S3-S6 in acceptable yields (25-70 %). Suzuki-Miyaura couplings using diverse boronic acids provided the desired final products 1 a-n and 2 a-n (15-86 %).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the synthesis of the benzofuran derivatives, a one-pot, two-step reaction was implemented. [40] Eu(OTf) 3 catalyzed the epoxide opening with various amines followed by nucleophilic aromatic substitution using Cs 2 CO 3 to generate the benzofurans S3-S6 in acceptable yields (25-70 %). Suzuki-Miyaura couplings using diverse boronic acids provided the desired final products 1 a-n and 2 a-n (15-86 %).…”
Section: Resultsmentioning
confidence: 99%
“…Suzuki-Miyaura couplings using diverse boronic acids provided the desired final products 1 a-n and 2 a-n (15-86 %). [40] In the synthesis of the benzopyran derivatives, the protection of the epoxyalcohol as a TBS ether generated silyl ethers S7-S8 in excellent yields (96-100 %). In order to override the selectivity for benzofuran formation, the alcohol resulting from the epoxide opening was protected as a benzyl ether with good yields (40-85 % over 2 steps).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently described a microwave-assisted method to selectively access 3-amino-2,3-dihydrobenzofurans. 13 However, this route did not en- We have previously shown that a one-pot, microwaveassisted, acid-catalyzed epoxide opening and subsequent intramolecular nucleophilic aromatic substitution reaction could be used to access benzofuran scaffolds. 13 Conveniently, both of these reactions can also be carried out separately to give a readily isolable diol as an intermediate.…”
mentioning
confidence: 99%